Antiglutamatergic therapy in Alzheimer's disease - effects of lamotrigine - Short communication - TANRIDAĞ, TÜLİN (SPRINGER-VERLAG WIEN, 1998)
It has been proposed that excitotoxic damage by glutamatergic hyperactivity is responsible for neurodegeneration in Alzheimer's disease. Lamotrigine (LTG) inhibits presynaptic glutamate release and is considered to be effective in treatment of other neurodegenerative disorders by its cerebroprotective properties. We used LTG in 11 patients with the diagnosis of probable Alzheimer's disease. 300 mg/day administration of LTG improved word recognition, naming and depressed mood on Alzheimer Disease Assessment Scale (ADAS).
Keywords: lamotrigine; glutamate; glutamate release; excitatory neurotransmitter; Alzheimer's disease; neuroprotection; therapy; GLUTAMATE; DEMENTIA; CORTEX; SCALE